Higher concentration insulins: an overview of clinical considerations. Issue 5 (4th July 2017) - Reid, Timothy S.; Schafer, Fryn; Brusko, Cynthia
ABSTRACT: Three higher concentration insulin products (insulin lispro 200 units/mL, insulin degludec 200 units/mL, and insulin glargine 300 units/mL) received US Food and Drug Administration (FDA) approval in 2015. Although human regular insulin 500 units/mL (U-500) was approved in 1997, a pen and dedicated U-500 syringe became available in 2016. These products offer more treatment options for the increasing numbers of patients requiring insulin to achieve and maintain glycemic targets. Higher concentration insulins have some unique safety and efficacy considerations. Important considerations when transitioning patients from the 100 unit/mL concentration (U-100) to the higher concentration include bioequivalence, pen dose increments, and pen appearance. Bioequivalent insulins have similar pharmacokinetic properties and no dose adjustments are expected when transitioning from the U-100 to the higher concentration. In contrast, higher concentration insulins with different pharmacokinetic and pharmacodynamic properties compared with the U-100 formulation may require dose adjustments. In order to provide safe and effective therapy to patients with higher daily insulin dose requirements, it is important for healthcare professionals to become very familiar with the characteristics of and differences between each of the higher concentration insulins. This paper highlights differences between the U-100 and higher concentration insulins and focuses on practical aspects of use.